THE EFFECT OF TEACHER EDUCATION, TRAINING, AND WORK DISCIPLINE ON THE PERFORMANCE OF RELIGIOUS TEACHERS IN ISLAMIC ELEMENTARY SCHOOL IN SOUTH TANGERANG CITY (Dialog, 2016)
This study aims to determine the factors that affect the performance of religious teachers in Islamic Elementary School in South Tangerang City. The study employed causal survey method with the population of 85 religious teachers in Islamic Elementary School in South Tangerang City. Given that the sample is less than 100 participants, the respondents in this study is the total sample (the whole population). Data were collected using a questionnaire to measure the variables of teacher performance, education and training, and work discipline. The coefficient of reliability (alpha value) is consecutively 0.8074; 0.7126. The results indicate that, first, there is a direct and significant effect of education and training to the teacher performance, indicated by the value Ã¾ = 1.030 with a regression equation Y = 28.529 + 1,030X1, r1y correlation coefficient = 0.917, and the coefficient of determination R square = 0.841, or 84,1%. Second, there is a positive and significant impact of education and training on work discipline, shown by the p-value = 0.00